2013
DOI: 10.1590/s2176-94512013000300018
|View full text |Cite
|
Sign up to set email alerts
|

Time of guard of orthodontic records versus legal time for their prescription

Abstract: It is advised to return part of the clinical records to their rightful owners by means of an itemized receipt. The Term upon Completion reflects the patient's awareness and could be considered by the CCP as the initial term of the prescription time, because it implicates that the patient recognizes the quality of service provided and satisfactory results achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…In Brazil, the Dental Code of Ethics[11] requires that dentists archive the dental records of their patients indefinitely,[12] and the violation of the ethical standards set forth in the document may result in penalties that range from a warning to revocation of professional license.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Dental Code of Ethics[11] requires that dentists archive the dental records of their patients indefinitely,[12] and the violation of the ethical standards set forth in the document may result in penalties that range from a warning to revocation of professional license.…”
Section: Discussionmentioning
confidence: 99%
“…Patient records are also supplemented by various tests required by the orthodontic treatment, such as radiographs, plaster impressions, photographs (intra and extra oral), radiograph tracings, and other specific diagnostic aids. These stored records help the orthodontist to re-evaluate any progress in the treatment in a spotted time and can be legal aid in front of judiciary [8].…”
Section: Record Keepingsmentioning
confidence: 99%
“…The present research showed that most professionals request control radiographs. Authors (BENEDICTO et al, 2010;PARANHOS et al, 2013) affirm that besides being mandatory items for orthodontic documentation, panoramic and incisors periapical radiographs should be requested every six months to follow-up on root resorption.…”
Section: Legal Issues Vs Professional Liability Insurancementioning
confidence: 99%
“…The documents and exams requested to the patient, such as radiographs (outlined), photographs, and plaster models (by the volume occupied), may be handed out to the legitimate interested party -not to third parties -, with a delivery receipt properly signed (PARANHOS et al, 2013), and the professional may file these information digitally.…”
Section: Introductionmentioning
confidence: 99%